Care provision and dependency in long-stay institutions - O'Shea, Eamon; Murray, Peter (Economic & Social Studies, 1997)
This paper investigates the empirical relationship between the dependency characteristics of elderly residents and the amount of care provided by health care professionals in a selected number of long-stay institutions in Ireland. The results point to a weakness of the generalised Guttman scale measure of physical dependency in predicting fine levels of care. Only the highest category of the scale has a significant influence on care provision. Other aspects of dependency are also considered in the paper. The most intriguing result arising from the consideration of other dependency variables is the negative relationship between co-operation and care provision. Type of institution also influences the provision of care, demonstrating the importance of the supply-side in models of this type.
Keywords: Care provision; Dependency; Long term care; Ireland